Integrating Technology by Malaysian Polytechnic Students in Utilizing Institutional Repositories: A Continuous Study Employing the UTAUT Framework - Kiprawi Sani; Jati Kasuma Ali; Noor Zaidi Sahid; Yusman Yacob; Nelson Lajuni (Human Resource Management Academic Research Society (HRMARS), 2024)
This paper is to report the progress of the research which aims to determine the acceptance of Malaysian polytechnic students towards Institutional Repository for learning. User acceptance of a new technology or innovation is carried out to assess the level of user acceptance and response and has been adopted user acceptance theories such as Unified Theory and Use of Technology (UTAUT) and added attitudes as an external variables. This study hold significant important for the visibility and sustainability of the Institutional Repository platform for the long term. However, the study of technology acceptance at the Institutional Repository in Malaysian polytechnics seems to still lack research data related to user acceptance for the Institutional Repository platform to ensure that this service is implemented effectively to assist library users. Objective of this study is to examine user acceptance towards Institutional Repository platform for facilitating the learning process among Malaysian polytechnics students. This quantitative empirical study will conducted at four Malaysia polytechnic in Malaysia which is used propulsive sampling technique which is Politeknik Sultan Abdul Aziz Shah, Politeknik Kuching Sarawak, Politeknik Seberang Perai and Politeknik Kota Bharu. The three constructs of the UTAUT model are used as direct determinants of behavior intention and added with attitudes as external variables as moderators. Data analysis will use SPSS for descriptive and Smart PLS SEM for structural equation modelling. Next, there are needs of the user’s acceptance study towards Institutional Repository platform since it has never implemented. The benefits of technology adoption will reflect students' perceptions of its adoption and the stakeholders who should be responsible for planning, managing and promoting digital libraries for the benefit of students